Recent Studies in Turbine Blade Cooling - Je-Chin Han (International Journal of Rotating Machinery)
Gas turbines are used extensively for aircraft propulsion, land-based power generation, and industrial applications. Developments in turbine cooling technology play a critical role in increasing the thermal efficiency and power output of advanced gas turbines. Gas turbine blades are cooled internally by passing the coolant through several rib-enhanced serpentine passages to remove heat conducted from the outside surface. External cooling of turbine blades by film cooling is achieved by injecting relatively cooler air from the internal coolant passages out of the blade surface in order to form a protective layer between the blade surface and hot gas-path flow. For internal cooling, this presentation focuses on the effect of rotation on rotor blade coolant passage heat transfer with rib turbulators and impinging jets. The computational flow and heat transfer results are also presented and compared to experimental data using the RANS method with various turbulence models such as k-ε, and second-moment closure models. This presentation includes unsteady high free-stream turbulence effects on film cooling performance with a discussion of detailed heat transfer coef- ficient and film-cooling effectiveness distributions for standard and shaped film-hole geometry using the newly developed transient liquid crystal image method.